Desenvolvimento de um sistema para análise de integridade estrutural de equipamentos estáticos baseado em cad vps micro cracks e ultrassom - Ramos, Moacir Bispo (2009)
In general, the designs of equipment takes into account the effects and processes of deterioration it will undergo and arrives at an approximate useful life. However, changes in operational processes and parameters, the action of external agents, the kind of maintenance conducted, the means of monitoring, and natural and accidental occurrences completely modify the desired performance of the equipment. The discontinuities that occur in anisotropic materials often and due to different factors evolve from being subcritical to critical acquiring the status of defect and compromising the physical integrity of the equipment. Increasingly sophisticated technological means of detection, monitoring and assessment of these discontinuities are required to respond ever more rapidly to the requirements of industry. This paper therefore presents a VPS (Virtual Pipe System) computational tool which uses the results of ultrasonic tests on equipment, plotting the discontinuities found in models created in the CAD and CAE systems, and then simulates the behavior of these defects in the structure to give an instantaneous view of the final behavior. This paper also presents an alternative method of conventional ultrasonic testing which correlates the integrity of an overlay (carbon steel and stainless steel attached by welding) and the reflection of ultrasonic waves coming from the interface between the two metals, thus making it possible to identify cracks in the casing and a shift of the overlay